Intriguing Shadows: Decoding EDGAR ALLEN POE’S Stylistic Mastery in the Suspenseful World of THE MURDERS IN THE RUE MORGUE - Ur Rehman, Ziyad; Sabeen (Journal of Peace, Development and Communication, 2023)
Every human being has their own style of using language. Meaning is constructed through these unique styles of language use. Stylistic analysis of texts reveals how meaning is constructed through these unique styles of use of language in texts. This research delves into the stylistic elements employed by Poe in “The Murders in the Rue Morgue” and their profound impact on the creation of themes and the establishment of a morbid environment in his works. The study conducts an in-depth analysis of Poe's stylistic patterns, including phonetic, lexical, grammatical, and semantic analysis employing deep textual analysis techniques. The analysis of the story shows that Poe’s careful selection and manipulation of imagery, symbolism, diction, syntax, and phonetics contribute to the enduring power and fascination of his stories, making him a master of the macabre and a pioneer in the realm of Gothic literature. By examining the interplay between language and the human psyche, this research sheds light on the depths of fear and darkness within the human condition that Poe skillfully explores.